Progress of Research on Transformation of Chronic Pancreatitis to Cancer - Bangwei HUANG; Pengyuan WANG; Lianghao HU; Zhaoshen LI (Zhongliu Fangzhi Yanjiu)
The transformation from inflammation to cancer is a complex pathological process, in which the inflammatory state progresses to the formation of malignant tumors. Chronic pancreatitis (CP) is a progressively inflammatory and fibrosing disease, predominantly featuring acinar cell atrophy owing to the cellular damage and fibrosis of the pancreatic parenchyma. This review centers on elucidating how prolonged exposure to a chronic inflammatory environment prompts adaptive changes in acinar cells, which may ultimately lead to their conversion into cancerous cells. By delving into the pivotal role of acinar-to-ductal metaplasia, this article investigates the multi-stage pathway of CP progression into pancreatic cancer, as well as the underlying molecular regulatory networks. We aim to light on the profound mechanisms of CP's inflammation-driven carcinogenic transformation, and thus provide a scientific foundation for devising innovative preventive strategies and therapeutic interventions targeted at mitigating or halting this lethal conversion process.